A Summary of Charge-Coupled Devices for Astronomy. (4th January 2016) - Lesser, Michael
Abstract: Charge-coupled devices (CCDs) have been the most common visible and nearultraviolet imaging sensors in astronomy since the 1980s. Almost all major astronomical instrumentation utilizes CCD imagers for both scientific observations and the more routine tasks such as telescope guiding. In this short review, we provide a brief history of CCDs in astronomy and then describe their operation as they are most commonly implemented for scientific imaging. We discuss specialized CCD sensors which have been developed and effectively utilized in modern astronomical instrumentation. We conclude with an overview of the characterization of CCDs as performed in detector laboratories and at telescopes and discuss anticipated future advances.